The Sub-Gaussian Distribution of Currency Futures: Stable Paretian or Nonstationary? - So, Jacky C. (The Review of Economics and Statistics, 1987)
This study conducts an empirical test to examine wh ether the observed non-normal distribution of currency futures price changes isgenerated by the relationship between maturity and variability. In general, the author finds that the relationship between maturity and vari-ability is not suff icient to explain the observed non- normality. Although some amount of non-statio narity is present in the scale and in the characteristic exponent, the non-norma l stable Paretian distribution adequately describes futures price changes for mo st currencies and most contracts during the period covered in thisstudy Copyright 1987 by MIT Press.